Regulation of melanin production in fungi - Chhoker, Kamaldeep; Hausner, Georg; Harris, Steven D. (Frontiers in Fungal Biology, 2025)
Melanin is a dark macromolecule found in organisms ranging from animals to fungi and plants. In fungi, melanin is a secondary metabolite that is not essential per se for growth but does provide various benefits that facilitate adaptation to stressful conditions such as UV light, desiccation, oxygen radicals, and extreme temperatures. The biosynthetic pathways of most types of melanin are known and documented, but the regulation of those pathways is not well understood. In fungi, known pathways for melanin production include those directing the synthesis of 1,8-DHN melanin and L-DOPA melanin, as well as the tyrosine degradation pathway. Genetic studies have identified structural genes and enzymes that play a role in these different melanin biosynthesis pathways. Recent studies have focused on the roles of various transcription factors (TFs) and signaling circuits (e.g., cAMP/PKA and the HOG pathway) in regulating the expression of the biosynthetic pathways. The review will provide insights into what is known about these TFs and regulatory circuits in diverse fungi in an attempt to identify common themes.